2023
DOI: 10.3390/molecules28031339
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of pH Indicator Auxetic Hydrogel Skin Wound Dressing

Abstract: The benefits of enclosing pH sensors into wound dressings include treatment monitoring of wounded skin and early detection of developing chronic conditions, especially for diabetic patients. A 3D printed re-entrant auxetic hydrogel wound dressing, doped with pH indicator phenol red dye, was developed and characterized. The re-entrant auxetic design allows wound dressing adhesion to complex body parts, such as joints on arms and legs. Tensile tests revealed a yield strength of 140 kPa and Young’s modulus of 78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The use of auxetics in the biomedical field has become popular due to the use of auxetic biomaterials [10] [11]. An auxetic biomaterial is simply an auxetic structure manufactured from a material derived from a biocompatible material such as protein-based hydrogel [12]. It is most common for these structures to be produced with 3D printing methods [10] [12].…”
Section: Finite Element Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of auxetics in the biomedical field has become popular due to the use of auxetic biomaterials [10] [11]. An auxetic biomaterial is simply an auxetic structure manufactured from a material derived from a biocompatible material such as protein-based hydrogel [12]. It is most common for these structures to be produced with 3D printing methods [10] [12].…”
Section: Finite Element Analysismentioning
confidence: 99%
“…. Tsegay et al, 2023[12] presented an auxetic hydrogel skin pH indicator wound dressing as a smart band-aid or dressing. Using a phenol red dye in the hydrogel matrix of the material could help monitor pH changes in the vicinity of the wound to better indicate what treatment is required for the patient.…”
mentioning
confidence: 99%
“…Besides drug release, pH-responsive hydrogel wound dressings can also monitor wound healing. For instance, F et al [64] incorporated the pH indicator phenol red dye into a hydrogel to monitor wound healing through color changes due to pH shifts. O et al recently demonstrated a novel approach for incorporating pH-sensing capabilities into a cutting-edge hydrogel wound dressing composed of bacterial nanocellulose (BC) [65].…”
Section: Ph-responsive For Hydrogel Dressingsmentioning
confidence: 99%
“…pH-sensing 3D membranes: The pH of intact and non-infected skin is slightly acidic and typically varies between 4 and 6, while that of chronic wounds is typically in the range of 7 to 9. Hence, enclosing pH sensors into wound dressings has the potential to provide an assessment of the wound status, facilitating the detection of early-stage infections [ 121 ]. New studies are focusing on optimizing the sensitivity and response time of such sensors.…”
Section: Sensorsmentioning
confidence: 99%
“…Mirani et al [ 137 ] demonstrated the high regenerative efficacy of wound dressing by monitoring the infection and supporting wound healing via antibiotic and growth factor delivery investigations in mouse models. With the development of electronic information and image processing technology, binding pH sensors into regenerative 3D-printed membranes serves to elevate the treatment monitoring of wounded skin, which provides early detection of deteriorative chronic diseases and the release of regenerative drugs in real time [ 121 ]. By monitoring and providing effective responses to the healing stages, pH-responding sensors potentially give direct access to the wound status without disturbing the wound bed.…”
Section: Sensorsmentioning
confidence: 99%